University Students' Motives to Exercise According to the Self-Determination Theory - Kashef Zayed; Irene Frieze (Sultan Qaboos University, 2015)
The present study investigated exercise behavior and its motives among Sultan Qaboos University students. Self-determination theory was used to investigate the relationship between these motives and the actual exercise behavior. The study sample consisted of 263 students from the Faculty of Education at Sultan Qaboos University (129 male and 134 female). The participants completed two questionnaires: an exercise behavior questionnaire which was developed specifically for this study; and an Arabic version of the Exercise Motivation Inventory (EMI-2), which was developed by Markland and Ingledew. Descriptive statistics showed that 20% of male students and 77% of female students didn't participate at all in any sport and exercise activities; 45% of male students and 21% of female students participated moderately in sport and exercise activities (2-3 times a week); while 35% of the male students and 2% of the female students participated intensively in sport and exercise activities (almost on daily basis). Results indicated that intrinsic motives for exercise behavior (challenge, revitalization, health, affiliation and enjoyment) were common among the male participants. However, physically active females, extrinsic motivations (ill-health avoidance, positive health, revitalization, weight management, and appearance) were the major driving forces for their exercise behavior. Results of the current study provide support for the application of the self-determination theory within the Arab context.